Utilization Potential of Water Resources in Check Dams in Gansu Province - Wu Xiao; Jin Feng; Zhang Fu; Ma Rui; Wang Linli; Shen Hongtao (Shuitu baochi tongbao)
[Objective] The potential of check dams to retain silt and utilize water resources were analyzed in order to provide a basis for water resource utilization and management of check dams. [Methods] The current construction status, the quantity and spatial distribution of sediment retention, the utilization benefit, and the potential of water resources for check dams in sandy and coarse sand areas of Gansu Province were analyzed by investigation. [Results] By the end of 2019, 1 600 check dams had been built in Gansu Province, including 559 large dams, 452 medium dams, and 589 small dams. These dams controlled an area of 4 101 km2, with a total capacity of 481.95 million m3, of which the designed siltation capacity was 229.08 million m3. The current soil interception capacity of these dams was 142.87 million m3, accounting for 62.37% of the designed interception capacity. The interception amounts of large, medium, and small dams accounted for 80.86%, 13.21% and 5.93%, respectively, of the total interception by check dams. The Jinghe River basin, the main channel of the Yellow River, the Liujiaxia Reservoir area, the Weihe River basin, and the Taohe River basin accounted for 71.46%, 13.91%, 12.72%, 1.91%, respectively of the total interception. Due to a decrease in the soil erosion modulus, the actual mean interception capacity of large dams accounted for 43.88% of their designed capacity after 17 years of siltation (the average designed siltation period was 15 years). The actual mean interception capacity of medium-sized dams accounted for 38.81% of their designed capacity after 13 years of siltation (the average designed siltation period was 10 years). The remaining storage capacity of the check dams in Gansu Province was 86.21 million m3 that can be used to store water for utilization. Currently, water in check dams is mainly used for drought emergencies, efficient water-saving irrigation of farmland and orchards, diversified land management, comprehensive economic development, livestock and poultry breeding, and comprehensive development and utilization of water. In the future, 147 check dams can be used to reserve water for human drinking, irrigation, and aquaculture (fish ponds) in Qingyang, Pingliang, Tianshui, and Anding of Dingxi. [Conclusion] In order to meet the social demand for check dams in the local rural revitalization and high-quality development strategy, for areas with water storage and water needs, the design standards of new dams should be improved, and high-standard check dams that can store water for a long time should be built. The large and medium-sized check dams that have been built will be upgraded reconstruction to ensure the safety of the check dam body, flood control and water resources utilization. More importantly, it is necessary to establish an early warning mechanism for the risk management and control of check dams to effectively resolve the contradiction between water storage and flood control management in check dams in water-deficient areas.